Dampak Komitmen Organisasi, Self Efficacy Terhadap Konflik Peran Dan Kinerja Karyawati PT. HM Sampoerna Tbk. Di Surabaya - Handayani, Wiwik (Jurnal Riset Ekonomi dan Bisnis, 2008)
There are many things need motivated married woman to work. Indonesian woman show high performance in education and working word. People have psychologist pressing from environment. It causes problem in family position (her role) and duty in his job and family as mother. This research has done to know the effect of organization commitment, self efficacy to role conflict and her performance as an employment at PT. Sampoerna, Tbk.Variabel use in this research are organization commitment, self efficacy, role conflict and performance as production employment in PT. Sampoerna, Tbk. Purposive Sampling is used to find sampel. We have 150 sampel. We ask  200 people to fill questioner form. Data analyze by Structural Equation Modeling (SEM).The statistic analyze show that organization commitment has negative effect and significant to role conflict and performance, Self efficacy has positive effect and significant to role conflict and performance, and Role conflict has negative effect and significant to performance  in production department employment of PT. Sampoerna, Tbk.Keywords: Organization Commitment, Self Efficacy, Role Conflict, Performance